Bleeding After Musculoskeletal Surgery in Hospitals That Switched From Hydroxyethyl Starch to Albumin Following a Food and Drug Administration Warning. (October 2020) - Krishnamoorthy, Vijay; Ellis, Alan R.; McLean, Duncan J.; Stefan, Mihaela S.; Nathanson, Brian H.; Cobert, Julien; Lindenauer, Peter K.; Brookhart, M. Alan; Ohnuma, Tetsu; Raghunathan, Karthik
Abstract : BACKGROUND: While US Food and Drug Administration (FDA) black box warnings are common, their impact on perioperative outcomes is unclear. Hydroxyethyl starch (HES) is associated with increased bleeding and kidney injury in patients with sepsis, leading to an FDA black box warning in 2013. Among patients undergoing musculoskeletal surgery in a subset of hospitals where colloid use changed from HES to albumin following the FDA warning, we examined the rate of major perioperative bleeding post- versus pre-FDA warning. METHODS: The authors of this article used a retrospective, quasi-experimental, repeated cross-sectional, interrupted time series study of patients undergoing musculoskeletal surgery in hospitals within the Premier Healthcare Database, in the year before and year after the 2013 FDA black box warning. We examined patients in 23 "switcher" hospitals (where the percentage of colloid recipients receiving HES exceeded 50% before the FDA warning and decreased by at least 25% in absolute terms after the FDA warning) and patients in 279 "nonswitcher" hospitals. Among patients having surgery in "switcher" and "nonswitcher" hospitals, we determined monthly rates of major perioperative bleeding during the 12 months after the FDA warning, compared to 12 months before the FDA warning. Among patients who received surgery in "switcher" hospitals, we conducted a propensity-weighted segmented regression analysis assessing differences-in-differences (DID), using patients in "nonswitcher" hospitals as a control group. RESULTS: Among 3078 patients treated at "switcher" hospitals (1892 patients treated pre-FDA warning versus 1186 patients treated post-FDA warning), demographic and clinical characteristics were well-balanced. Two hundred fifty-one (13.3%) received albumin pre-FDA warning, and 900 (75.9%) received albumin post-FDA warning. Among patients undergoing surgery in "switcher" hospitals during the pre-FDA warning period, 282 of 1892 (14.9%) experienced major bleeding during the hospitalization, compared to 149 of 1186 (12.6%) following the warning. In segmented regression, the adjusted ratio of slopes for major perioperative bleeding post- versus pre-FDA warning was 0.98 (95% confidence interval [CI], 0.93–1.04). In the DID estimate using "nonswitcher" hospitals as a control group, the ratio of ratios was 0.93 (95% CI, 0.46–1.86), indicating no significant difference. CONCLUSIONS: We identified a subset of hospitals where colloid use for musculoskeletal surgery changed following a 2013 FDA black box warning regarding HES use in sepsis. Among patients undergoing musculoskeletal surgery at these "switcher" hospitals, there was no significant decrease in the rate of major perioperative bleeding following the warning, possibly due to incomplete practice change. Evaluation of the impact of systemic changes in health care may contribute to the understanding of patient outcomes in perioperative medicine.